2020
DOI: 10.1128/msystems.00313-20
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota-Produced Indole-3-Propionic Acid Confers the Antihyperlipidemic Effect of Mulberry-Derived 1-Deoxynojirimycin

Abstract: Hyperlipidemia has been intensively focused on by researchers around the world owing to its major contribution to cardiovascular diseases. Various evidence reveals that women are more susceptible than male counterparts to dyslipidemia, making sex-dependent therapeutic strategies and drugs urgently needed. In the present work, we demonstrate that DNJ, the main active component of mulberry leaves, exerts an obvious female-preferential antihyperlipidemic effect through specifically enriching Akkermansia and Clost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 49 publications
0
28
1
Order By: Relevance
“…76 In addition, cell culture studies reported that IPA decreases paracellular permeability by increasing expression of tight junction proteins and strengthening the mucus barrier in intestinal epithelial cells 77 and lowers lipid accumulation in liver cells. 78 Thus, these findings suggest that feeding of dietary insects’ cuticles has improved the gut barrier function, likely as a consequence of the modulation of the gut microbiota composition. In agreement with this, a recent study clearly demonstrated that chitin oligosaccharides – one of the main components of insects’ cuticles – strongly increased the expression of tight junction-related genes, such as tight junction protein ( Tjp ) 1 and Tjp2 and occludin in the distal small intestine of mice.…”
Section: Discussionmentioning
confidence: 86%
“…76 In addition, cell culture studies reported that IPA decreases paracellular permeability by increasing expression of tight junction proteins and strengthening the mucus barrier in intestinal epithelial cells 77 and lowers lipid accumulation in liver cells. 78 Thus, these findings suggest that feeding of dietary insects’ cuticles has improved the gut barrier function, likely as a consequence of the modulation of the gut microbiota composition. In agreement with this, a recent study clearly demonstrated that chitin oligosaccharides – one of the main components of insects’ cuticles – strongly increased the expression of tight junction-related genes, such as tight junction protein ( Tjp ) 1 and Tjp2 and occludin in the distal small intestine of mice.…”
Section: Discussionmentioning
confidence: 86%
“…The beneficial effects of IPA on multiple diseases such as steatohepatitis, hyperlipidemia, and diabetes have been demonstrated ( 18 , 30 , 31 ). IPA also modulates astrocyte activation and neuroinflammation and inhibits neuronal death induced by endoplasmic reticulum stress ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…IPA could maintain the integrity of the intestinal barrier via pregnant X receptor and toll-like receptor 4 [ 38 ]. Meanwhile, Li et al observed that 1-deoxynojirimycin treatment significantly increased the level of IPA in the feces of mice, and simultaneously enriched Akkermansia [ 39 ]. These results revealed that A. muciniphila might be able to utilize the tryptophan metabolites, which are produced by other commensal intestinal flora.…”
Section: Discussionmentioning
confidence: 99%